Obtaining life-cycle cost-effective facilities in the Department of Defense - Samaras, Constantine (RAND National Defense Research Institute, 2013)
The Department of Defense (DoD) constructs, operates, and maintains a large number of facilities, such as barracks, hangars, and administrative buildings. The research interviewed more than 30 individuals with varying roles and perspectives on the military construction (MILCON) and facility sustainment processes. The research team also reviewed MILCON protocols, policies, documents, and contracts to characterize the process of obtaining life-cycle cost-effective facilities. At each step of the MILCON process, there are different entities, roles, incentives, and barriers to obtaining life-cycle cost-effective facilities. Aligning the incentives of these various entities, and removing funding, information, timing, and resource barriers, would enable DoD to obtain facilities that are more life-cycle cost-effective.